Virtualna javnost v luči postmodernih konceptualizacij javnega mnenja - Oblak, Tanja (Družboslovne razprave, 1998)
Recent debates about the formation and expression of public opinion direct special interest to the meaning of media and media representations. These studies differ considerably from the classical understanding of public opinion because they regard the role of the media in a very specific way: the media are important as the mediators of media representations, which therefore accomplish their functions in two directions. On the one side, media representations, as modern discursive practices, constitute the "postmodern public". This "virtual public" becomes coherent through symbols. On the other side, media representations represent symbolic dimension of public opinion, but only under certain conditions; when they are persuasive, spectacular and politically relevant. Through the exact description of the main thesis and by the example of public opinion polls as modern media representations, this paper tries to point out advantages and risks of such concepts. We accept that changes in the practices of media representations are adequate mechanisms for the expression of public opinion, but only when they are understood within the present social context. What we find more questionable is the interpretation of media representations as a sufficient substitute for rational discussion. These mechanisms are not inherent to the issues, but rather to the mode of their representation. "Virtual public", constructed through such a process, in our opinion, is not a simple successor of the active public, but rather its unavoidable companion.
Keywords: javno mnenje; communication medium; mediji; množični mediji; mass media; communication; komuniciranje; informacijska tehnologija; information technology; navidezna resničnost